APPLICATION FOR DATA INTEGRATION BETWEEN SECTIONS AT THE CLASS I IMMIGRATION OFFICE OF TPI CIREBON - Priati Assiroj; Arief Febrianto; Qodrat Ilhami (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
1st Class Cirebon Immigration Office have developed various information systems to support the immigration services in the region. The problem arise from having various information systems is the possibility of data redundancy, ineffective, and duplicated data during the interdivisional data input process. Dependency of interdivisional data in immigration service demand the immigration office to create the data integration system, integration data means data from each divisions will be integrated/collected in one integrated database based on one time entry data process. This research aims to develop an innovation of interdivisional data integration design at 1st Class Cirebon Immigration Office. Data integration aims to increase the service effectiveness by reduce the data entry volume in the service process and increase data validity. The data is taken by descriptive qualitative method, and integration system designed using Software Development Life Cycle (SDLC) method. In this project “Inter- Division Data Integration Apps in the 1st Class Cirebon Immigration Office” the web-based application has been successfully created. The one time entry data-concept connected each divisions menu on the application and integrated one another by the real-time, this application will surely simplify and accelerate the inter-division data recapitulation process especially for the monthly- report making process. This web-based application can make the working flow more efficient, effective, can reduce the data redundance, and increase the validity of data.